Rancangan Interface Komunikasi Data Aeronautical Fixed Telecomunication Network Menggunakan GSM Gateway Berbasis Arduino - Moch. Ilyas; Yuyun Suprapto; Totok Warsito; Romma Diana P. (Jurnal Penelitian)
The design of data transmission is made with the intention of later as media data delivery AFTN at low cost, utilizing the network provider using the GSM GATEWAY will get a solution to the problem of how to transmit data AFTN when an aerodrome does not have the means of VSAT and the airport does not have a network AFTN. The working principle of this circuit is to change the output signal DB9 serial port on the teleprinter news format ITA2 (5n1) is converted to the module MAX3232 to be transformed into TTL voltage level, which is a TTL input data that can be processed by a microcontroller Arduino Mega 2560. Output of Arduino Mega was converted back to the module MAX3232 from TTL to Serial, then the data is then converted digital signal into an analog signal by using Wavecom M1306B Modem Serial Q2406B. This analog signal is then sent to the destination. Once the information from the transmitter wavecom analog signal received by the receiver with wavecom modem, the signal is converted back by module MAX3232 Serial to TTL which will be connected to the Arduino Uno microcontroller and connected with a PC software in which there are accepted as news ticker